Hot carrier relaxation in CdTe via phonon-plasmon modes - Zhong, Yinpeng; Schlichting, Ilme (Journal of physics. Condensed matter, 2017)
Carrier and lattice dynamics of laser excited CdTe was studied by time-resolved reflectivity for excitation fluences spanning about three orders of magnitude, from 0.064 to 6.14 mJ cm −2 . At fluences below 1 mJ cm −2 the transient reflectivity is dominated by the dynamics of hybrid phonon-plasmon modes. At fluences above 1 mJ cm −2 the time-dependent reflectivity curves show a complex interplay between band-gap renormalization, band filling, carrier dynamics and recombination. A framework that accounts for such complex dynamics is presented and used to model the time-dependent reflectivity data. This model suggests that the excess energy of the laser-excited hot carriers is reduced much more efficiently by emitting hybrid phonon-plasmon modes rather than bare longitudinal optical phonons.
Gesehen am 12.09.2018